1985
DOI: 10.1007/bf02552884
|View full text |Cite
|
Sign up to set email alerts
|

Popliteal entrapment syndrome

Abstract: A case of a type of popliteal entrapment syndrome that does not include an anomalous course of the popliteal artery is presented. In situ thrombosis secondary to entrapment-induced stasis was the presumed cause of ischemic symptomatology. Thorough knowledge of the possible causes of entrapment and biplane angiography (of the popliteal artery) with provocative maneuvers often are required for diagnosis. As in our patient, surgical release of the entrapment can lead to complete resolution of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The vessel may appear normal at rest but show a characteristic extrinsic indentation on the lateral wall when angiogram is done with the foot in active plantar flexion (1,2). Occasionally, the vessel may be totally occluded due to repeated trauma produced by the entrapping muscle (4). Diagnosis in such cases may have to be clinical, with confirmation at surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The vessel may appear normal at rest but show a characteristic extrinsic indentation on the lateral wall when angiogram is done with the foot in active plantar flexion (1,2). Occasionally, the vessel may be totally occluded due to repeated trauma produced by the entrapping muscle (4). Diagnosis in such cases may have to be clinical, with confirmation at surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive diagnostic studies, such as CT and Doppler US, have been used frequently in PAE syndrome in recent years [1,13]. Intra-arterial DSA has the disadvantage of being a relatively invasive technique, and it is also in-sufficient by itself in the evaluation of PAE syndrome, as it cannot show the nature of the tissue leading to occlusion of the artery.…”
Section: Discussionmentioning
confidence: 99%
“…Typically a young patient presents with intermittent claudication. (Gaines et al, 1985;Williams et al, 1986). Although entrapment of the popliteal artery may be present in up to 3.5% of individuals (Gibson et al, 1977), clinical diagnosis is uncommon and successive papers have shown that this syndrome causes stenosis or occlusion of the popliteal artery with a frequency not exceeding 1% (Hamming and Vint, 1985;Represa et al, 1986).…”
Section: Introductionmentioning
confidence: 96%